Design of ultralong-life Li–CO2 batteries with IrO2 nanoparticles highly dispersed on nitrogen-doped carbon nanotubes. Issue 7 (31st January 2020) - Wu, Gang; Li, Xue; Zhang, Zhang; Dong, Peng; Xu, Mingli; Peng, Hongliang; Zeng, Xiaoyuan; Zhang, Yingjie; Liao, Shijun
Abstract : IrO2 nanoparticles highly dispersed on N-doped carbon nanotubes pave a promising way to deploy an efficient cathode catalyst for ultralong-life Li–CO2 batteries. Abstract : Li–CO2 batteries have gained tremendous popularity since they can not only realize the eco-friendly utilization of the greenhouse gas CO2, but also offer high theoretical energy density. However, they still suffer from several problems, such as high overpotential and poor cycling life. High-efficiency electrocatalysts for carbon dioxide reduction and Li2 CO3 decomposition play a critical role in Li–CO2 batteries. In this work, nitrogen-doped carbon nanotubes modified with ultrafine IrO2 nanoparticles (IrO2 -N/CNT) were introduced into the cathode of Li–CO2 batteries. The batteries with the IrO2 -N/CNT cathode exhibited high specific capacity (4634 mA h g −1 ), low charge platform and overpotential (3.95 V/1.34 V), and ultralong cycling life (more than 2500 h/316 cycles at 100 mA g −1 with a fixed capacity of 400 mA h g −1 ). It is speculated that the high performance of the IrO2 -N/CNT cathode is closely related to the superior catalytic activity of highly dispersed ultrafine IrO2 nanoparticles and the nitrogen-doped carbon nanotube network, which not only enhances the electronic conductivity and the capture ability of CNT for Li atoms/CO2, but also promotes reactions between Li + /CO2 and C/Li2 CO3 . This work paves a promising way to deploy an efficient cathode catalyst for ultralong-life Li–CO2 batteries.